POPULASI DAN PERSENTASE SERANGAN LARVA Spodoptera exigua Hubner PADA TANAMAN BAWANG DAUN DAN BAWANG MERAH DI DESA AMPRENG KECAMATAN LANGOWAN BARAT - Meilani Paparang; Ventje V. Memah; James B. Kaligis (Universitas Sam Ratulangi, 2016)
ABSTRACKThis research aims at indentifying the ratio of the population and the percentage of Larva.attack on leeks and shallot plant. This research was taken in Ampreng Village, Langowansubdistrict, Minahasa Regency. This research had been taking for two month, i.e. that isMarch to April 2016 . The research was taken by using the survey method on leeks andshallot plants in Ampreng village, Langowan subdistrict. The researcher had used thediagonally slicing method i.e determining 5 sub plots on the location of taking the sample.Taking the sample had been done by using the interval of time along one week for three timesof observation. The finding of the research showed the average of the highest population ofLarva S. exigua went to Shallots i.e 1.44 tails, meanwhile the population of Larva on leeksonly got 0,67 tail. The highest average of Larva S. exigua attack went to Shallots plants, i.e.28,07 %, meanwhile leek plant only 14,81 %. The result of the independent analysis testâ€œsample T-testâ€ showed there are found the real differences of the population and thepercentage of Larva S. exigua attack on leeks and shallot plants.Kata kunci : Population, Percentage, Leek, Shallot, S. exigua